Re-theorizing literacy practices complex social and cultural contexts - Bloome, David; Castanheira, Maria Lucia; Leung, Constant 1950-; Rowsell, Jennifer 1969- (New York Routledge, 2019)
"Moving beyond the current theories on literacy practices, this edited collection sheds new light on the complexities inherent to the social, cultural, and ideological contexts in which literacy practices are realized. Building on Brian V. Street's scholarship, contributors discuss literacy as innately social and ideological, and examine how the theorizing of literacy practices has evolved in recognition of the diverse contexts in which written language is used. Breaking new intellectual and theoretical ground, this book brings together leading literacy scholars to re-examine how educational and sociocultural contexts frame and define literacy events and practices. Drawing from the richness of Brian V. Street's work, this volume offers insights into fractures, tensions, and developments in literacy for scholars, students, and researchers"--Provided by publisher.
Introduction: lost in our meditations about re-theorizing literacy practices across complex social and cultural contexts / Jennifer Rowsell, David Bloome, Maria Lucia Castanheira, and Constant Leung -- Fashioning literacy as social / David Bloome, Judy Kalman, and Matthew Seymour -- Literacy as a social practice: new models and new realities / Gunther Kress and Jennifer Rowsell -- Ideologies languaged into being: examining conversations on schooled and -- Religious literacies ideologies / Maria Lucia Castanheira -- Making of narrative: understanding young children's story writing in social contexts / MinJeong Kim and Kelly King -- Ideological battles over Quechua literacy in Perâu: from the authority of experts to the innovation of youth / Virginia Zavala -- Literacy teaching and learning in school as polyphonic: a close examination of a lesson focused on fun home, the graphic memoir and musical / Mollie V. Blackburn -- Academic literacies as laminated assemblage and embodied semiotic becoming / Paul Prior and Andrea Olinger -- Literacy research as ideological practice: knowledge, reflexivity and the researcher / Uta Papen -- Testing practice in a southern school / Mastin Prinsloo and Lara-Stephanie Krause -- Reading philosophy critically: agentive classroom enactment / Lynne Isham and Constant Leung -- Approaches to academic literacy instruction: classifications, conflicts and new directions / Ursula Wingate -- Literacy and the time being / Michiko Hikida -- Faith, culture and identity: the everyday literacy practices / Zanib Rasool -- Examining our blind spots: personhood, literacy, and power / Stephanie Power-Carter and Bita Zakeri -- Conclusion: literacy as social and cultural in the future perfect tense / Brian Street with David Bloome, Maria Lucia Castanheira, Constant Leung, and Jennifer Rowsell.
Includes bibliographical references and index.
Keywords: Literacy -- Social aspects